El proceso enseñanza aprendizaje de la cultura física y su incidencia en la formación deportiva y la masificación de los deportes, en los alumnos de las escuelas fiscales del sector sur oriental del cantón Loja, período lectivo 2012 – 2013. Lineamientos propositivos - Cabrera Sisalima, Verónica Lorena (2014)
Throughout the history of economic , political and social development of man, has been in constant contact with the sport , so primitive civilizations like the Egyptian, Sumerian , Mayan, Inca, Roman , Greek enter other , even with the current the conduct of major sporting events worldwide as they are the Olympics have made the sport a supplement to their daily lives. This research work entitled " PROCESS TEACHING - LEARNING PHYSICS CULTURE AND ITS IMPACT ON TRAINING AND SPORTS MASSIFICATION IN STUDENTS OF TAX SCHOOLS SECTOR SOUTH EAST CANTON Loja , PERIOD LECTIVO . 2012 - 2013 GUIDELINES proactive " the general aim of the research is guided : Determine how the teaching - learning process of Physical Culture affects athletic training and sports overcrowding in schoolchildren South East sector . Canton of Loja, school year , school year 2012 - 2013 , in order to obtain alternatives to finding solutions according to the reality of this sector ( propositional guidelines.) The specific hypotheses raised in this research are: 1. The low process learning of Physical Culture negative impact on athletic training students in the schools of the South East area of Loja Canton, academic year 2012-2013; 2. Insufficient teaching-learning process of Physical Culture negative impact on mass sports in schoolchildren South East area Loja Canton, school year 2012-2013 . The processes used were hypothetical - deductive method, analytical explanatory statistical; also to prepare the analysis was descriptive method came to. The techniques were applied to the survey were teachers and students from the schools of South East sector Loja Canton, through the questionnaire designed for the purpose. The research involved five teachers and 88 students. The main results that were reached are: The schools involved in the research such as: Joint Tax School " Dr. Luis Emilio Rodriguez "from Landangui , Escuela Fiscal Mixta "Manuel Esteban Godoy" of Nangóra, Escuela Fiscal Mixta "Elvia Jimenez Gonzalez" from Rumizhitana, Escuela Fiscal Mixta "Maria Montessori" and the School "Victor Mercante" Malacatos is not have specialist teachers in Physical Culture and those who are being made and improvised general teachers, which does not allow proper sports training students and proper mass sports in this area of Loja Canton.